2017
DOI: 10.1007/s00122-017-2919-z
|View full text |Cite
|
Sign up to set email alerts
|

A mutant in the CsDET2 gene leads to a systemic brassinosteriod deficiency and super compact phenotype in cucumber (Cucumis sativus L.)

Abstract: A novel dwarf cucumber mutant, scp-2, displays a typical BR biosynthesis-deficient phenotype, which is due to a mutation in CsDET2 for a steroid 5-alpha-reductase. Brassinosteroids (BRs) are a group of plant hormones that play important roles in the development of plant architecture, and extreme dwarfism is a typical outcome of BR-deficiency. Most cucumber (Cucumis sativus L.) varieties have an indeterminate growth habit, and dwarfism may have its value in manipulation of plant architecture and improve product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…Studies have shown that genes related to leaf cell size and division, SAM differentiation, miRNA, and auxin polarity content influence leaf shape (Mao et al ). Cucumber has a wide diversity of leaf shapes, and several studies have indicated that the molecular mechanisms underlying leaf shape in this plant involve SAM border control, nucleoside bisphosphate phosphatase, the BR regulatory pathway, miRNA, and auxin receptors (Ding et al ; Gao et al ; Hou et al ; Xu et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that genes related to leaf cell size and division, SAM differentiation, miRNA, and auxin polarity content influence leaf shape (Mao et al ). Cucumber has a wide diversity of leaf shapes, and several studies have indicated that the molecular mechanisms underlying leaf shape in this plant involve SAM border control, nucleoside bisphosphate phosphatase, the BR regulatory pathway, miRNA, and auxin receptors (Ding et al ; Gao et al ; Hou et al ; Xu et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The SCL1 ( SMALL AND CORDATE LEAF 1 ) gene was cloned by BSA (bulked segregant analysis)‐seq technology, but its regulatory mechanism remains unclear (Gao et al ). Using map‐based cloning, Hou et al () identified CsDET2 ( de‐etiolated‐2 ) as the candidate gene affected in the cucumber dwarf mutant scp‐2 ( super compact‐ 2). CsDET2 is involved in the brassinosteroid (BR) regulatory pathway, and the loss‐of‐function mutant has wrinkled leaves.…”
Section: Introductionmentioning
confidence: 99%
“…A steroid 5α-reductase, named as DEETIOLATION 2 (DET2), is responsible for the C5 reduction in Arabidopsis ( Chory et al, 1991 ; Li et al, 1996 ; Fujioka et al, 1997 ; Li et al, 1997 ; Noguchi et al, 1999 ). Paralogs of DET2 in different plant species have also been identified, such as in soybean, cotton, cucumber, pea, and morning glory ( Suzuki et al, 2003 ; Nomura et al, 2004 ; Luo et al, 2007 ; Hou et al, 2017 ; Huo et al, 2018 ).…”
Section: Br Biosynthesis Pathwaysmentioning
confidence: 99%
“…Brassinosteroid (BR) are steroid hormones which regulate plant development, physiology, and responses to biotic and abiotic stresses (Hou et al, 2017;Lv et al, 2018;Unterholzner et al, 2015;Wang et al, 2013). Studies on mutants with defects in BR biosynthesis or signaling demonstrated that BR plays essential roles in nearly all phases of plant development, as these mutants show multiple developmental defects, such as reduced seed germination, extreme dwarfism, photomorphogenesis in the dark, altered distribution of stomata, delayed flowering and male sterility (Gomes, 2011;Hou et al, 2017;Jiang et al, 2013;Lv et al, 2018;Unterholzner et al, 2015;Wang et al, 2013). Brassinosteroids stimulate seed germination and BR signaling is required to overcome inhibition of germination by ABA (Steber and McCourt, 2001).…”
Section: Singular Enrichment Analysismentioning
confidence: 99%